Desenvolvimento de hidrogéis a base de amigo para suporte de nanopartículas de prata - Moreira, Thaciana Dos Santos (2025)
Natural polymers, such as starch, are widely used due to the reactive groups in their structure, allowing modifications that alter their chemical, physical and biological properties, which enables several applications. Hydrogels, formed by three-dimensional polymer networks, have a high water absorption capacity and can serve as a support for different compounds. Their vast potential and growing interest in nanostructured materials have driven research in this area. The polymer networks of hydrogels favor the dispersion and stabilization of silver nanoparticles. Thus, the objective of this work was to produce a starch-based hydrogel with the insertion of silver nanoparticles in its structure. The hydrogels were prepared considering some parameters such as time and temperature in the gelatinization and retrogradation processes. Structural changes resulting from the incorporation of silver nanoparticles and silver ions were also analyzed. It is noteworthy that the freezing and thawing cycles of the hydrogel are essential for the formation of ice crystals that precede the lyophilization step. Raman spectroscopy and X-ray diffraction techniques were used for molecular and structural characterization, respectively. In addition, the hydrogels were subjected to swelling tests, antimicrobial tests, and morphological characterization by atomic force microscopy and scanning electron microscopy (SEM) with energy dispersive detector (EDS), which allowed the identification of the material composition. The results highlighted the importance of crystalline reorganization in the retrogradation process, influenced by freezing and thawing cycles. These cycles allowed the observation of the behavior of amylose and amylopectin molecules, revealing changes in the polymer network of the hydrogel and their relationship with the stability and structural properties of the material. Microbiological tests showed that the hydrogel with silver ions inhibited the growth of Escherichia coli, while the hydrogel with silver nanoparticles did not show inhibitory action. The swelling test indicated the water absorption capacity, with emphasis on the hydrogel with commercial AgNP (274%) and synthesized AgNP (222%). In addition, the morphological analysis revealed that the hydrogel has a flat surface with the presence of steps.The results show that the crystalline reorganization, influenced by the freezing and thawing cycles, is essential for the retrogradation and properties of the hydrogel. The action of silver ions conferred an antimicrobial effect against Escherichia coli, unlike silver nanoparticles, although the absorption capacity did not demonstrate this functionality. The study contributes to the development of hydrogels with adjustable properties for applications in materials engineering.